Pengembangan dan Pelatihan Aplikasi Cari Kerja DisnakerTrans Provinsi Sumatera Selatan - Susanto Susanto; Putu Rika Melani (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This community service activity aims to support the digital transformation of public services in the employment sector through the development and training of a web-based job-seeker application for the Department of Manpower and Transmigration in South Sumatra Province. This innovation was introduced as a solution to the previous system’s limitations, which relied heavily on administrators for job postings and updates. Research Methodology: The implementation combined user-based system development with staff training. The development process involved needs analysis, interface design, testing, and the integration of an employer-account feature for companies to manage job vacancies independently. Training was conducted face-to-face on December 5, 2023, for six Disnakertrans staff members through interactive lectures and hands-on sessions. Results: The newly added feature successfully improved the efficiency and transparency of publishing job vacancies. Companies can now post, update, and monitor vacancies independently, while Disnakertrans staff have improved their technical and managerial competencies in managing the digital employment system. Conclusions: This activity makes a tangible contribution to supporting the digital transformation of regional public services through the integration of software development and capacity building, which can be replicated by other local government agencies in Indonesia. Limitations: The activity was limited to the provincial level and has not yet been expanded to district or city offices. A long-term evaluation of system adoption and sustainability has not been conducted. Contributions: This activity contributes to regional digital transformation by integrating software development and capacity-building strategies, providing a replicable model for other local government institutions seeking to enhance public service digitalization.